Effect of Pore Size on the Ion Electrosorption and Hydrogen/Deuterium Electrosorption Using Sodium Chloride in H2O and D2O. Issue 16 (16th December 2019) - Zhang, Yuan; Srimuk, Pattarachai; Husmann, Samantha; Chen, Ming; Feng, Guang; Presser, Volker
Abstract : In nanoconfinement, the reversible electrochemisorption of hydrogen extends the voltage window of aqueous electrolytes. This process has been well studied for different aqueous electrolytes but not compared to the performance of heavy water. Herein, we study hydrogen and deuterium electrosorption on a porous carbon electrode under negative polarization using sodium chloride as the salt. As electrodes, we use microporous carbons with an average pore size in the sub-nanometer range and, for comparison, mesoporous carbon nanotube bucky paper. We show that the hydrogen electrochemisorption and gas evolution processes are more pronounced than for deuterium while the same potential is applied. Our data confirm lower ion mobility of D2 O compared to H2 O, and a shift of the reversible charging and discharging process toward more negative potentials.